Achieving child-health-related Millennium Development Goals : the role of infrastructure - Fay, Marianne...[et al.] (2005)
Provides an empirical analysis of the determinants of three child-health outcomes related to the MDGs viz. the infant mortality rate; the child mortality rate; and the prevalence of malnutrition. Concludes that better access to basic infrastructure services has an important role to play in improving child-health outcomes.